2023
DOI: 10.1002/zamm.202200384
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution and statistical analysis of the unsteady hybrid ferrofluid flow with heat generation subject to a rotating disk

Abstract: The goal of this study is to examine the significant parameter of unsteady Fe 3 O 4 -CoFe 2 O 4 /H 2 O with heat generation flowing on a rotating disk using numerical and statistical approaches. The mathematical model respected to time-dependent is first transformed into a set of ordinary differential equations (ODEs) by using similarity variables. The computation is done by employing bvp4c method utilizing MATLAB software. The validation of present model and the output is done by direct comparison with the es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The distinction between the two studies is that [21] examined an unsteady flow scenario using CoFe 2 O 4 as the magnetic particles. By utilizing the concept of response surface methodology in order to scrutinize the physical parameters, Khashi'ie et al [22] examined the unsteady flow of Fe 3 O 4 -CoFe 2 O 4 /water while considering the effects of heat generation through a rotating disk. Souayeh et al [23] studied the impacts of activation energy, gyrotactic microorganisms, and electromagnetohydrodynamics on Au-Ag/blood flow in a symmetric peristaltic channel.…”
Section: Introductionmentioning
confidence: 99%
“…The distinction between the two studies is that [21] examined an unsteady flow scenario using CoFe 2 O 4 as the magnetic particles. By utilizing the concept of response surface methodology in order to scrutinize the physical parameters, Khashi'ie et al [22] examined the unsteady flow of Fe 3 O 4 -CoFe 2 O 4 /water while considering the effects of heat generation through a rotating disk. Souayeh et al [23] studied the impacts of activation energy, gyrotactic microorganisms, and electromagnetohydrodynamics on Au-Ag/blood flow in a symmetric peristaltic channel.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yahaya et al, [30] used RSM to correlate the heat transfer rate with the testing parameters and found that the suction parameter has a positive impact on this coefficient. Furthermore, RSM and statistical data analysis have been applied to various fluid flow problems, as discussed in previous studies [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the constantly developing need for hybrid ferrofluid, excellent research has been conducted, as reported by Refs. [ [38] , [39] , [40] ].…”
Section: Introductionmentioning
confidence: 99%